Fluidized Bed Combustion of Pelletized Sewage Sludge in a Pilot Scale Reactor. Issue 9 (2nd September 2019) - Cammarota, A.; Cammarota, F.; Chirone, R.; Ruoppolo, G.; Solimene, R.; Urciuolo, M.
ABSTRACT: Fluidized bed combustion stems out as one of the most feasible technology to burn sewage sludge. However, the performances of bubbling fluidized bed combustors fueled with pelletized sewage sludge are still lacking at pilot scale. In this work, an experimental campaign on a pilot scale bubbling fluidized bed combustor (FBC370), was carried out to investigate the effect of sewage sludge pelletization on combustion behavior. The gaseous and particulate emissions during stable thermal regimes for thermal power ranging roughly from 50 to 65 kWth were measured. Under the experimental conditions investigated, a stable and efficient combustion behavior was obtained in terms of low emissions of unburnt species, but a train of cleaning processes is necessary to reduce gaseous and particulate emissions. A two stage de-dusting system for the capture of fine and ultrafine particles and the proper units for the abatement of the NOx, SO2, and HCl produced in high concentrations are needed. The temperature profile in the post-combustion zone and stable combustion conditions are critical for the formation of dioxins. On the whole, the sewage sludge pelletization plays an important role in fuel conversion and in the formation of particulate and gaseous macro pollutants. In particular, it is observed that: 1) the partitioning between fly and bottom ash significantly changes reducing the generation of fines particles produced; 2) the stratified combustion of volatile matter and char particles can be enhanced at low fluidization velocity favoring bed agglomeration phenomena; 3) NO emissions are affected by ash accumulation inside the bed when efficient fuel mixing conditions are achieved.